Prospek dan Strategi Pemasaran Kerupuk Itik “Mama Ami” di Desa Kota Raden Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara - Miranda Romaully Br. Sitanggang; Arief Hidayatullah; Murliani Murliani (Rawa Sains: Jurnal Sains STIPER Amuntai, 2013)
This research aimed to selling forecast duck chip for five year later and know what is the matter with “Mama Ami’s” duck chip business in Kota Raden village with analysis the strengths, weaknesess, opportunities and threats. This is Research use case study method. The Instrument what to use research is SPSS software for forecase marketing, to make a marketing strategy researcher use IFE matric,EFE matric, IE matric. Based on the result forecast selling duck chip refer to selling increase continou. IFE matric result total score 3,134 and 2,521 for score EFE Matric. The score to those disposition IV sel on IE matric, that is grow and build. This disposition just up to intensive strategy dan integration strategy.